Do Label Still Matter? Blurring boundaries between administrative and criminal law. The influence of the EU - Weyembergh, Anne (European Studies, 2014)
Criminal law has considerably evolved in the last few decades. A number of new trends have challenged the traditional features of "modern criminal law".